A SCANNER IN THE WORKS. - ZYGMUNTOWICZ, SAM (Strad, 2009)
The article discusses scientific principles and testing used to analyze violins and the quality of the sound they produce. The use of sound testing equipment and computed tomography (CT) scan technology to study violin construction and quality is examined. The value of such studies for violin makers is explored, particularly regarding possible effects on acoustic quality.